Second Harmonic Generation: Second Harmonic Generation Circular Dichroism from Self‐Ordered Hybrid Plasmonic–Photonic Nanosurfaces (Advanced Optical Materials 3/2014). Issue 3 (March 2014) - Belardini, Alessandro; Benedetti, Alessio; Centini, Marco; Leahu, Grigore; Mura, Francesco; Sennato, Simona; Sibilia, Concita; Robbiano, Valentina; Giordano, Maria Caterina; Martella, Christian; Comoretto, Davide; de Mongeot, Francesco Buatier
<x xml:space="preserve">Abstract</x> A. Belardini et al. find that hybrid structures composed by self‐ordered dielectric nanospheres partially covered by gold nanocrescents produce an efficient second harmonic generation signal due to the cooperative effect of localized plasmon excitation and a 2D Bragg grating. Asymmetries in the geometric shape of the gold nanocrescents induce a circularly polarized optical response. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>